Documenting the digital transformation of African agriculture: Use and impact of digital technologies among agricultural intermediaries - Heike Baumüller; Ubi Ikpi; Emmanuel Tetteh Jumpah; Geoffrey M. Kamau; Alpha Kergna; Lawrence Mose; Abdoulaye Nientao; Rose Omari; Dayo O. A. Phillip; Beatrice D. Salasya (University of Bonn, Center for Development Research (ZEF), 2022)
Agricultural intermediaries perform important functions in the African food and agriculture sector. Digital solutions targeted at these intermediaries could improve their service delivery while helping digital agricultural (D4Ag) service providers cover the last mile to producers. To determine how to empower agricultural intermediaries with digital technologies, it is important first to understand how they are already making use of and are impacted by these technologies in their professional activities. To this end, data was collected through 1,571 in-person interviews with extension workers, output dealers and input dealers in Ghana, Kenya, Mali and Nigeria. The results show that intermediaries make extensive use of ICTs in their work, much more so than the low adoption rates of D4Ag solutions would suggest. Mobile phones clearly dominate the digital technologies, most commonly smartphones, which are often used daily. Three areas of impact can be identified. First, ICTs facilitate information sharing between intermediaries and other value chain actors which emerged as the main activity and benefit across the three groups. Second, ICTs facilitate networking among value chain actors. In the case of dealers, these networks are mainly used for two-way business transactions while extension agents take advantage of ICTs to interact and share information with a wide range of actors. Third, ICTs reduce transaction costs for input and output dealers through better access to information about buyers, sellers and prices, better timing of produce / input purchases, faster payments from customers and reduced travel times. Given the widespread use of ICTs among agricultural intermediaries, D4Ag service providers can capitalize on intermediaries' existing digital skills, technological capacities and digitally enabled networks to expand their reach, in particular to producers who are still not universally accessible via ICTs, but also to other actors in the African food and agriculture sector.
Keywords: 330; Landwirtschaft; Digitalisierung; Informationstechnik; Innovationsakzeptanz; Subsahara-Afrika